TEACHING ENGLISH TO YOUNG LEARNERS AS A SECOND LANGUAGE - Diyora Madjidova Alisherovna (Western European Studies, 2024)
This article explores effective methods for teaching English as a second language to young learners. It discusses various approaches, such as immersive learning, games, and interactive activities, and examines their impact on language acquisition. The study highlights the importance of incorporating age-appropriate techniques to engage young learners effectively. Furthermore, it emphasizes the significance of creating a supportive learning environment conducive to language development. The findings underscore the need for continuous adaptation and innovation in ESL pedagogy to meet the diverse needs of young language learners.
Keywords: Second language acquisition; young learners; English language teaching; methods